Ketidaksetaraan Gender dalam Program FTV Suara Hati Istri: Suatu Kajian Analisis Wacana Kritis Norman Fairclough - Setiawan, Dandi; Wibisono, Bambang; Astuti, Soekma Yeni (Journal of Feminism and Gender Studies, 2022)
The FTV Suara Hati Istri episode Aku Hanya Boneka di Sangkar Emas Suamiku is interesting to study, because there are gender inequalities in it. Using qualitative research with the approach of Norman Fairclough, this study aims to describe: (1) the dimensions of the text of gender inequality discourse, (2) the practical dimensions of gender inequality discourse, and (3) the dimensions of sociocultural practice. The research data was combined with the free-of-conversation listening technique, analyzed descriptively analytically, and the results were presented informally. The results of the study indicate that there are texts or discourses on gender inequality in FTV through the production of texts and the responses of viewers who consume them. The sociocultural practice that is displayed is a strong patriarchal culture in married life.